A motiváció és a fluktuáció összefüggései egy termelő vállalat esetében - Csiki Eszter (2019)
I wrote my examination paper about the correlations between the motivation and fluctua-tion in a producing company. The biggest part of me choosing this topic was to process a central and actual question from nowadays. Researches and articles can confirm the im-portance of this topic which prove the key factors are in human resources. In this past year I spent my time being an intern in the examined company, so I was able to see what kind of serious problems they are dealing with in the area of dealing with their human resources caused by the motivation of their employees. This is how in this dis-sertation I’m looking for the answer of how the motivation of the employees can affect the fluctuation of the organization. This way this examination didn’t just give me valuable in-formation but for the leadership of the organization too. First the theoretical field of human resources management and the fluctuation was reviewed, then I made my research based on theory. During the primary research I used two methods to explore the motivation and satis-faction of employees. First, I sent out a questionnaire with fifteen questions to the em-ployees of the organization, which was based on the Herzberg's two-factor model. With this questionnaire I compared the satisfaction of the individual workgroups with each oth-er to reveal which group is causing the root problem. Then to confirm the results of this questionnaire I interviewed one person from each workgroup. To examine the fluctuation I used these researching methods. Based on the data provided by the company, I analysed the fluctuation level of the organization by docu-ment analysis which I confirmed with my observations during my internship. Based on the results I got I came to conclusions, which made it possible to formulate the correlation between the motivation and the fluctuation in the case of the examined company. Finally, I formulated suggestions for the company to improve the satisfaction and motivation of its employees and as well as to reduce fluctuations at the same time.